Measuring environmentally sustainable growth in agriculture across the EU countries based on Solow residual-based MFP - Vitunskienė, Vlada; Lauraitienė, Lina (Socialiniai tyrimai, 2022)
Scientific publications on environmentally sustainable or green growth in agriculture are increasingly becoming more important but empirical research is scarce. In empirical studies, the most commonly accepted way to assess environmentally sustainable or green growth in agriculture is based on measures of total factor productivity (TFP) or multifactor productivity (MFP) growth. Both measures are important for analytical and monitoring tools that can help to better understand the factors affecting output growth as well as the determinants of changes in production factors (labour and produced capital) in agriculture. Growth of TFP or MFP is achieved through the application of technologies and advanced production practices that result in higher output from the same amount, or lower inputs (labour and produced capital). Conventional TFP and MFP are not suitable for the assessment of environmentally sustainable growth in agriculture because both indicators do not include environmental variables such as environmental pollution and natural capital. There is a lack of comparative empirical studies between EU countries. This study focuses on the problem of measuring environmentally sustainable growth in agriculture. The aim of this study is twofold: firstly, to develop a framework for the assessment of environmentally sustainable growth in agriculture, based on information collected in public databases; and secondly, to empirically analyse environmentally sustainable growth in agriculture in EU countries over the long period. The environmentally adjusted multifactor productivity (EAMFP) growth measure was applied to assess environmentally sustainable growth in agriculture of the EU’s countries. For analysis, the environmental pollution of agricultural production was expressed as net GHG emissions, and natural capital was expressed as the quality-adjusted agricultural land area. The research was conducted using literature overview, decomposition technique and cluster analysis method. The 28 EU countries (including the United Kingdom, which was a member of the EU until January 1, 2020) were included in the empirical analysis. The analysis covered the period between 2005 and 2019 and a five-year average annual change rates (2005-2009 and 2015-2019 respectively) were used to compare the environmentally sustainable growth in agriculture between the beginning and the end of the considered period, as is common in most agricultural growth studies. The findings show that pollution-adjusted GDP growth in agriculture was achieved in less than a five of the EU countries at the beginning of the considered period, and in most of the EU countries at the end of the considered period. In most of the EU countries, the environmentally sustainable growth in agriculture was mainly determined by technological progress, while the slow change in environmental pollution (net GHG emissions) did not have a significant contribution to agricultural growth in all EU countries. Following the hierarchical clustering method, three significantly different clusters of the EU countries were identified in terms of gross added value growth and technological progress in agriculture of EU countries in the context of environmentally sustainable growth.